Análise da contribuição dos fundos setoriais destinados à agricultura para o desenvolvimento do Estado do Rio Grande do Norte - Machado, Kalina Barreto (2014)
Historically, innovation is considered a key element for competitiveness and economic growth of countries, and contribute to face the emerging challenges, such as increased global demand for food, social inequality and climate change. Following this logic, the Brazilian government adopted a policy of science, technology and innovation (ST & I), supported by qualified for the generation of new knowledge and technologies focused on biotechnology research human resources. The proceeds from the Agribusiness Sector Fund (CT-Agro), not only ensure the leadership of Brazil in world trade in agricultural commodities, as has been contributing to the increase in per capita income from the northeastern states. Thus, considering the dynamism of the state of Rio Grande do Norte in the horticulture sector, the purpose of this study was to analyze the contribution of the CT -Agro resources for the growth of the state and to improve the social and environmental indicators. In the methodology, we adopted a model of linear regression with panel data to estimate the average effects of elasticity (CT-Agro) explanatory variable with respect to per capita GDP (dependent variable). Funds invested in agribusiness, in the period from 2000 to 2009, among the 27 states, corresponding to a sample of 270 observations were analyzed. Among the statistical methods used to estimate the coefficients, Method of Fixed Effect, was the most suitable for the large adjustment of the data (R2 = 99%). The results showed, however, that resources for agribusiness cause positive effects to increase the income of the Natal economy. It can be concluded that investments in STI, give greater dynamism and efficiency in the production chain, and may be reflected in social and environmental benefits